(untitled) (Future Cities and Environment, 2025)
This research is to understand the students’ perception on reusing salvaged materials and to propose a sustainable approach for Higher Education Institution. The main thrust of this study is the amount of wastage from students work which are often left over after every assignment, that contributed to serious problems such as space issue, safety concerns, and visually unpleasing. The lack of understanding that each material, which has a significant value and the potential of reusing by integrating it as educational resource as a sustainable solution. This study is conducted to 853 students from the School of Architecture and Built Environment (SABE) at UCSI University, Malaysia. Hence, the main objective of this research is to identify what are the suitable recovering programs that could provide a potential sustainable solution towards the campus. A quantitative method approach using questionnaire survey as primary data to achieve the research objective. The finding of this research can contribute to better understanding on revaluing materials, prolonging its usage and the potential of implementing a circular material resource centre.